New development for aorto bifemoral bypass – a clampless and sutureless endovascular and laparoscopic technique. (June 2014) - Segers, Bernard; Horn, David; Bazi, Michel-Olivier; Lemaitre, Jean; Van Den Broeck, Vanessa; Stevens, Etienne; Roman, Alain; Bosschaerts, Thierry
The classic procedure for aortobifemoral bypass is open surgery. Laparoscopy has been accepted by several authors as a minimal invasive alternative for aortoiliac occlusive disease. The totally retroperitoneal laparoscopic procedure has been described as an alternative to the transperitoneal approach. Whatever the approach, the aortoprosthetic anastomosis is a major difficulty making those techniques unpopular despite obvious advantages for the patients. We report a clampless and sutureless approach for the proximal anastomosis of a totally retroperitoneal laparoscopic aortobifemoral bypass using an EndoVascular REtroperitoneoScopic Technique (EVREST). This approach was proposed to a 56-year-old man with severe aortoiliac occlusive disease. There was no indication for endovascular re-vascularization. The patient was placed in a 30° right lateral decubitus position. The dissection of the retroperitoneal space was performed and the infrarenal aorta was exposed. A bifurcated graft was inserted into the retroperitoneal space. Under videoscopic control the prosthetic limbs were brought to the groins. The main body of the graft was connected on the left side of the aorta by an intra and extra aortic covered stent-graft. This connection was performed without the use of an aortic clamp and without suture. The femoral anastomoses were performed by classic open surgery.